L'impératif en français et en anglais contemporains - Danon-Boileau, Laurent; Morel, Mary-Annick; Perrin, Isabelle (HERMES - Journal of Language and Communication in Business, 1992)
As a deontic mode of enunciation, the imperative excludes any operation which implies a certain degree of agreement between speaker and addressee - presupposition, referential construction, etc. In order to make up for this fundamental disjunction, the speaker resorts to a range of compensatory devices such as the use of person desinences, the ethical dative, the position of clitic pronouns or the function of the first person plural. Yet an imperative utterance is also related to the declarative context in which it occurs, and this sometimes causes co-locution to give way to co-enunciation - witness the problem of negative imperatives, or markers of discourse consistency such as voyons in French. This twofold theoretical approach is here presented as applying to the French language, and then put to the test of the English language.